Memahami Dinamika Bekerja dalam Ketidakpastian: Tinjauan Fenomenologis Pengalaman Bekerja Pengemudi Ojek Online - Luqman Tifa Perwira; Muhammad Hidayat (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
Employees of high technology company often facing rapid and unpredictable changes. This qualitative research aims to explore further how workers with high uncertainty working environment develop their strategies to be survived in this kind of environment. Online ojek driver works in high uncertainty environment where they have no clear employment status. The technology company who employs them only see them as a business partner which their relationship with the company could be terminated anytime. This qualitative research is conducted with phenomenological approach. Six ojek online driver respondents were chosen with minimum criteria: has been working in this field minimum 1 year, play a role as the main income earner in the family, and has the main job as online motor driver. Through a qualitative method with phenomenological approach, data analyzed by data reduction process resulted in five main themes: environmental uncertainty, task identity, values, strategy, and hope and themes of strategy to overcome those work situations and nature. Then the researcher developed an essential description or comprehensive construction about the meaning and the essence of the subjects’ experiences.